2003
DOI: 10.2337/diacare.26.2.385
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes Mellitus

Abstract: OBJECTIVE -To examine anxiety levels of women diagnosed with gestational diabetes mellitus (GDM) and to compare these with glucose-tolerant (GT) women at similar stages of pregnancy.RESEARCH DESIGN AND METHODS -Prospective longitudinal study conducted on 50 women with GDM and 50 GT women. All women completed the Mental Health Inventory (MHI-5) forms and the Speilberger State-Trait Anxiety Inventory (STAI) at the beginning of the third trimester, antepartum, and 6 weeks postpartum. Specific questions were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 18 publications
3
75
0
Order By: Relevance
“…In an Australian cohort, Rumbold and Crowther 16 found that women with GDM had negative perceptions about their health after screening for GDM. In another Australian cohort, however, Daniells et al 17 found that women with GDM had higher anxiety levels than women without GDM at the beginning of the third trimester, but that the groups were similar antepartum and 6 weeks postpartum. The authors speculated that any worry initially caused by the diagnosis was adequately addressed by treatment plans.…”
Section: Discussionmentioning
confidence: 92%
“…In an Australian cohort, Rumbold and Crowther 16 found that women with GDM had negative perceptions about their health after screening for GDM. In another Australian cohort, however, Daniells et al 17 found that women with GDM had higher anxiety levels than women without GDM at the beginning of the third trimester, but that the groups were similar antepartum and 6 weeks postpartum. The authors speculated that any worry initially caused by the diagnosis was adequately addressed by treatment plans.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, women with GDM were more anxious than women without GDM, as shown by a report by Daniells et al 27. However, the anxiety did not sustain if interventions were given27. In another report, Crowther et al 4.…”
Section: Discussionmentioning
confidence: 95%
“…This makes it possible to balance the potential adverse effects generated by the tests (anxiety, psychological distress, and future perception of health) (25)(26)(27) and potential benefits considering individual risk factors and discussing them with each patient.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%